Effects of liquid organic fertilizer (LOF) derived from banana peels and tempeh waste on the growth and yield of peanut plants (Arachis hypogaea L.) - Riyanti, Riyanti (Contributions of Central Research Institute for Agriculture, 2024)
This study, conducted at the Experimental Garden of the Faculty of Agriculture, Amir Hamzah University, Medan, aimed to evaluate the effects of liquid organic fertilizer (LOF) derived from banana peels and tempeh waste on peanut plant growth and yield. The study employed a factorial RBD (randomized block design), examining 2 factors. The first factor involved varying concentrations of LOF from banana peels: P0 = control (no application), P1 = 500 ml/plot, P2 = 1000 ml/plot, and P3 = 1500 ml/plot. The second factor assessed LOF from tempeh waste at different levels: T0 = control (no application), T1 = 0.750 liters of tempeh waste/1 liter of water/plot, T2 = 1.5 liters of tempeh waste/1 liter of water/plot, and T3 = 2.25 liters of tempeh waste/1 liter of water/plot. Parameters observed included plant height, number of branches, flowering age, number of pods per plant, number of filled pods per plant, weight of 100 seeds per plot, and production per plot. Results showed significant effects of tempeh waste-derived LOF on plant height, flowering age, number of pods per plant, number of filled pods per plant, and production per plot. Particularly, Level T3 (2.25 liters of tempeh waste/1 liter of water/plot) yielded optimal results across all parameters. Conversely, the application of LOF from banana peels showed no significant impact on observed parameters, and no interaction was observed between the two treatments.